Understanding and effectively addressing breast cancer in African American women: Unpacking the social context. Issue 14 (29th February 2016) - Williams, David R.; Mohammed, Selina A.; Shields, Alexandra E.
Abstract : Black women have a higher incidence of breast cancer before the age of 40 years, more severe disease at all ages, and an elevated mortality risk in comparison with white women. There is limited understanding of the contribution of social factors to these patterns. Elucidating the role of the social determinants of health in breast cancer disparities requires greater attention to how risk factors for breast cancer unfold over the lifecourse and to the complex ways in which socioeconomic status and racism shape exposure to psychosocial, physical, chemical, and other individual and community‐level assaults that increase the risk of breast cancer. Research that takes seriously the social context in which black women live is also needed to maximize the opportunities to prevent breast cancer in this underserved group. Cancer 2016;122:2138–49 . © 2016 American Cancer Society . Abstract : Insufficient attention has been paid to how risk factors for breast cancer in African American women begin in childhood and are closely tied to the conditions in which they live and work. Future research needs to pay additional attention to how researchers, clinicians and the larger society can best understand and address the myriad factors linked to racial status that are associated with breast cancer risk among African American women.